Inequalities in access to education: A socio-educational intervention with migrant children and youth - Casquilho-Martins, I.; Matela, T. (ICERI2021 Proceedings, 2021)
Education plays a central role in citizens' lives, in their socialisation processes and in their life projects. The importance of access to quality educational systems is a pillar of fundamental rights and a factor to social and sustainable development. However, immigrant children and young people find themselves in a position of social asymmetry in often discriminatory host societies, aggravated in crisis contexts. This study aims to analyse strategies for socio-educational intervention with immigrant children and youth in contexts of inequalities in access to the right to education. We used a documental analysis of the current legislation in Portugal, secondary statistical data through national and international databases and we interviewed professionals in the socio-educational intervention. The results show Portugal is a host country in which migrants’ integration has improved, namely regarding intervention in school settings. The progress of policies and programmes for integrating young immigrants has contributed to the realisation of the right to education, as well as to their social development. Thus, there is an evolution in the indicators and intervention strategies that should be strengthened considering the impacts of the migrant and pandemic crisis, which increases the vulnerability of migrant children and young people.